Effect of Co and Mo Loading by Impregnation and Ion Exchange Methods on Morphological Properties of Zeolite Y Catalyst - Didi Dwi Anggoro; Nur Hidayati; Luqman Buchori; Yayuk Mundriyastutik (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Coal tar can be used as an alternative raw material for the production of liquid fuels, such as: gasoline and diesel through hydrogenation and cracking process. Hydrogenation and cracking process requires a catalyst which has metal components for hydrogenation reaction and acid components for cracking reaction. In this study, the Co/Zeolite Y and Co-Mo/Zeolite Y catalysts were prepared by impregnation and ion exchange methods. Characterizations of the catalysts were carried out by X-Ray Diffraction (XRD) and gravimetric acidity. The catalysts were tested for coal tar conversion to liquid fuel under various temperatures, amount of catalyst and hydrogen flow rates in a fixed bed flow reaction system. Liquid fuels products were analyzed by gas chromatography (GC). The XRD Spectra indicated that the addition of Co and Mo metals did not affect catalysts structure, however it alters the percentage of crystallinity. The addition of Co metal using impregnation method caused reduction in crystallinity, while the addition of Mo caused improvement of crystallinity. The Co-Mo/Zeolite Y catalyst with highest crystallinity was obtained by loading using ion exchange method. The addition of Co and Mo metals caused increasing acidity. However, the increasing composition of Co and Mo loaded on Zeolite Y catalyst decreased the yield of liquid fuels from coal tar. It can be concluded that the yields of liquid fuels and the composition of gasoline fractions from hydrocracking of coal tar were highly dependent on acidity of the catalyst.